Time to Competency, Reliability of Flexible Transnasal Laryngoscopy by Training Level: A Pilot Study. (May 2015) - Brook, Christopher D.; Platt, Michael P.; Russell, Kimberly; Grillone, Gregory A.; Aliphas, Avner; Noordzij, J. Pieter
Objective: To determine the progression of flexible transnasal laryngoscopy reliability and competency in otolaryngology residency training. Study Design: Prospective case control study. Setting: Academic otolaryngology department. Subjects: Medical students, otolaryngology residents, and otolaryngology attending physicians. Methods: Fourteen otolaryngology residents from PGY-1 to PGY-5 and 3 attending otolaryngologists viewed 25 selected and digitally recorded flexible transnasal laryngoscopies. The evaluators were asked to rate 13 items relating to abnormalities in the oropharynx, hypopharynx, larynx, and subglottis. The level of concern and level of comfort with the diagnosis were assessed. Intraclass correlations were calculated for each topic and by level of training to determine reliability within each class and compare competency versus attending interpretations. Results: Intraclass correlation of residents compared to attending physicians demonstrated significant improvements by year for left and right vocal fold immobility, subglottic stenosis, laryngeal mass, left and right vocal cord abnormalities, and level of concern. Additionally, pooled vocal cord mobility and pooled results in categories with good attending reliability demonstrated stepwise improvement as well. For these categories, resident reliability was found to be statistically similar to attending physicians in all categories by PGY-3. There were no trends for base of tongue abnormalities, pharyngeal abnormalities, and pharyngeal and hypopharyngeal masses. Conclusions: Resident competency for flexible transnasal laryngoscopy progresses during residency to reliability with attending otolaryngologists by the PGY-3 year over key facets of the examination.